Irrigated vegetable production interventions in humanitarian emergencies: Mali country deep dive - Singh, Radhika; Minh, Thai Thi; Schmitter, Petra S. (International Water Management Institute, 2024)
In the context of Mali, a Sahelian country facing challenges of insecurity, political instability, and climate change, irrigated vegetable production (IVP) interventions have the potential to enhance resilience outcomes and reduce the vulnerabilities of households and communities by increasing incomes and improving nutritional outcomes. The recommendations for IVP interventions presented in this document are informed by an understanding of the complex sociopolitical landscape of Mali and address both challenges and opportunities.